2020
DOI: 10.1029/2019ja027293
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of Pi2 Pulsations Observed in the Upper Ionosphere Using Swarm Magnetic Field Data

Abstract: The properties of Pi2 pulsations observed in the upper ionosphere are studied using magnetic field data acquired by the Swarm A spacecraft in low Earth orbit and at the low-latitude Bohyun ground station (BOH, L = 1.3) for January 2014 to June 2015. From time intervals when Swarm A was on the nightside (magnetic local time (MLT) = 1800-0600 hr) and the BOH station was near midnight (MLT = 2100-0300 hr), we identified 621 Pi2 events in the horizontal H component of the BOH data. For each event we examined the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Neither E ϕ nor B ν exhibits an amplitude minimum in the L domain covered by the spacecraft. These results are consistent with the structures of the simulated f 2_sim mode (Figures 14j-14l) and confirm previous statistical results and their cavity mode interpretation (Park et al, 2020;Takahashi, Lee, et al, 2003;Takahashi et al, 1995;Teramoto et al, 2011Teramoto et al, , 2022.…”
Section: Radial Mode Structures At Midnightsupporting
confidence: 92%
See 4 more Smart Citations
“…Neither E ϕ nor B ν exhibits an amplitude minimum in the L domain covered by the spacecraft. These results are consistent with the structures of the simulated f 2_sim mode (Figures 14j-14l) and confirm previous statistical results and their cavity mode interpretation (Park et al, 2020;Takahashi, Lee, et al, 2003;Takahashi et al, 1995;Teramoto et al, 2011Teramoto et al, , 2022.…”
Section: Radial Mode Structures At Midnightsupporting
confidence: 92%
“…The disturbances can be bursty bulk flows with random periodicity. Previous statistical studies using satellite data found radially standing structures of compressional Pi2 waves in the inner magnetosphere, in favor of the cavity mode interpretation (Park et al., 2020; Takahashi, Lee, et al., 2003; Takahashi et al., 1995; Teramoto et al., 2011, 2022). However, there are Pi2 models that assume earthward‐propagating fast mode waves in the inner magnetosphere (Uozumi et al., 2009, 2020).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations